Inclusive physical education learning strategies for students with special needs in senior high schools: A literature revieweds In Senior High Schools: A Literature Review - Hidayat, Rezha Arzhan; Ihsan, Fadli; Nugroho, Sigit; Edmizal, Eval (Jurnal Pendidikan Jasmani Indonesia, 2024)
Inclusive physical education supports all students' social, emotional, and physical development, including those with special needs. With growing awareness of the importance of inclusivity in education, effective learning strategies to support the participation of students with special needs are becoming increasingly relevant, especially in senior secondary schools. This study aimed to explore and analyze various inclusive physical education learning strategies, focusing on how these approaches can improve the participation and learning outcomes of students with special needs. The methodology used was a systematic literature review, allowing for the comprehensive identification and analysis of strategies implemented and evaluated in inclusive physical education. Following PRISMA guidelines, the study selection process involved a structured literature search across multiple electronic databases, quality evaluation, and synthesis of findings from the selected studies. The literature review showed that inclusive approaches in physical education, including the use of assistive technology, adaptation of activities, and professional training for teachers, increase the engagement and participation of students with special needs and strengthen understanding and respect for diversity among all students. However, the study also identified challenges in implementing these strategies, such as lack of resources and inadequate teacher training. Inclusive approaches in physical education increase the engagement and participation of students with special needs and promote understanding and respect for diversity among all students. Successful inclusive learning strategies include applying assistive technology, modification of activities, professional training for teachers, and multidisciplinary collaboration. However, challenges in implementing these strategies were also identified, including a lack of resources, inadequate teacher training, and the need for more individualized curriculum adaptations. This research offers practical recommendations for educators and policymakers in developing more inclusive physical education practices, emphasizing the importance of student-centered approaches and close collaboration between schools, families, and communities to support students with special needs.